Performance evaluation of photovoltaic thermal systems using functionalized multi-walled carbon-based nano-enhanced phase change material - Reji Kumar, Rajamony (2023)
Photovoltaic (PV) technology enables direct conversion of solar energy to electricity for direct consumption. Photovoltaic conversion efficiency mostly decreases with increase in temperature of the PV system; henceforth temperature management is a key issue in PV system design. A hybrid photovoltaic thermal (PVT) system is a promising development, which facilitates extraction of heat energy and electrical energy simultaneous. Meanwhile, the challenge of using conventional water-based PVT systems is that they can only be used during the daytime. Integration of phase change materials (PCM) with PVT systems to regulate the temperature as well as to facilitate thermal energy storage is a popular and viable choice. However, the PCMs suffer from lower thermal conductivity which causes lower energy storage capabilities and lower heat transfer rates. Uniform dispersion of nanoparticles into the PCM enhances the thermal conductivity. Though, there are problems pertaining to dispersion stability of the nanoparticles; after a few cycles, they get agglomerated. The main objective of the present research is to synthesize and characterize the nano-enhanced phase change materials (NePCM); develop a PVT system, analyse the energy and exergy performance of the PVT system and to evaluate the performance of NePCM-integrated PVT system. A two-step method is used to synthesize the NePCMs using salt hydrate with a phase transition temperature of 50°C as PCM and functionalize multi-walled carbon nanotubes (FMWCNT) as nanoparticle. The prepared nanocomposites were characterized using fourier transform infrared spectrum, thermo-gravimetric analysis, differential scanning calorimetry, ultraviolet visible spectrum, thermal property analyser and thermal cycler to ensure their thermo physical properties. Energy and exergy analysis is carried out to evaluate the performance of the PVT system. PVT system is investigated using a parallel pipe flow channel as proposed in the current research investigation which acts as thermal collector for extracting the heat energy. To make a comparative analysis with the conventional PV systems, three new configurations namely PVT, PVT-PCM, and PVT NePCM with flowrates (0.4, 0.6 and 0.8 liter per minute (LPM), have been studied. Results obtained ensures chemical, physical and thermal stability of the prepared NePCM. FMWCNT at a weight concentration of 0.7% depicts thermal conductivity enhancement by 100% and light transmission decrement by 93.49% when compared with pure PCM. Furthermore, the nanocomposites were chemically and thermally stable, after 300 thermal cycles. Aforementioned NePCM with enhanced characteristics were integrated with PVT system for real time investigation. Results show that the electrical power output and efficiency to improve by 29.1% and 21.9% for the PVT-NePCM system. The maximum thermal efficiency of PVT, PVT-PCM and PVT-NePCM systems were found to be 73.1%, 74.99% and 75.42% at 0.4 LPM, respectively. Overall energy efficiency of the PVT, PVT-PCM and PVT-NePCM system were calculated to be 81.9%, 84.54%, and 85 % respectively at the optimized flowrate. On the contrary, the maximum exergy efficiency was found to be 12.37% for PVT-NePCM system. The developed system generates both electrical energy and thermal energy, which can be used for the remote areas. Further, Real time experimental study on NePCM integrated PVT system is needed to investigate the real time performance of PVT system.